Energy Utilization Behavior in Small Manufacturing Enterprises - Ramadani, Tariq (Omnia Tempus, 2023)
This study explores the behavioral dimensions of energy utilization within small manufacturing enterprises (SMEs), an often-overlooked sector in industrial energy policy and sustainability research. Recognizing that SMEs collectively contribute significantly to national energy consumption yet frequently operate with limited energy awareness, this study investigates how organizational behavior, managerial perceptions, and operational routines influence energy efficiency outcomes. Employing a qualitative methodology grounded in literature-based analysis, the research synthesizes findings from over 45 peer-reviewed journal articles, institutional reports, and case studies published between 2010 and 2024. Thematic content analysis was applied to extract key patterns and constructs related to SMEs' energy behavior, focusing on cognitive, structural, and cultural drivers. The findings reveal that while technical solutions such as energy-efficient technologies are available, their adoption is often hindered by behavioral constraints, including low managerial commitment, lack of employee engagement, and entrenched operational habits. Furthermore, institutional support mechanisms, such as energy audit programs and incentive schemes, have shown limited effectiveness due to their misalignment with SME capacities and realities. The study highlights that sustainable energy practices in SMEs require more than technology upgrades; they demand a shift in organizational mindset supported by behavioral interventions, capacity building, and localized policy design. By emphasizing the socio-organizational context of energy use, the study contributes to a growing body of interdisciplinary research and provides practical insights for policymakers, industry leaders, and sustainability advocates aiming to promote energy-conscious behavior in the small manufacturing sector.